The Intensity of The Constitution According to Dustur Saudi Arabia - Arlis, Arlis; Yuherlis, Neni (As-Siyasi: Journal of Constitutional Law, 2022)
Types of constitution in the perspective of Dustur Saudi Arabia is the main problem of the study. Article 1 of the Saudi Arabian State states that the State of Saudi Arabia is the daulah of Islamic Arabia, its religion is Islam, its constitution the Book of Allah Ta'ala and the Sunnah of His Messenger. The existing provisions show that the constitution according to Dustur Saudi Arabia is diverse, has dynamics and intensity. The purpose of the study is to uncover the intensity of the constitution. Normative legal research is used as a method with an approach to the substance and intensity of law. The results of the study revealed that the constitution according to Dustur Saudi Arabia has a great variety with superior intensity. The variety is Nizham Al-Asasi lil-Hukm, The Qur’an, the Sunnah, and the Median Constitution. This varieties have a very close and inseparable relationship. the al-Kitab is at the highest and strongest level, followed by the Sunnah, Dustur Medina, and Nizham Al-Asasi lil-Hukm. Saudi Arabia's dustur has an intensity that is in line with maqashid al-shari'ah which includes the protection of all aspects of world life and the hereafter. The novelty is the Book of Allah was the first and foremost written constitution in the world. The conclusion is that the intensity of the constitution according to the Dustur Saudi Arabia is very strong and highest level. The al-Kitab and the Sunnah are absolutely references in formulating, establishing, and implementing the constitution and all the rules.